Open access clinic providing HIV-I antibody results on day of testing: the first twelve months. Issue 6789 (8th June 1991) - Squire, S B; Elford, J; Bor, R; Tilsed, G; Salt, H; Bagdades, E K; Janossy, G; Griffiths, P D; Johnson, M A
Abstract : OBJECTIVES--To determine the sociodemographic profile, risk category, and prevalence of HIV-I infection among people attending a clinic providing counselling, medical advice, and results of HIV-I antibody testing on the day of consultation; to determine the stage of infection and peripheral blood CD4 cell count among attenders with detectable HIV-I antibodies. DESIGN--Analysis of prospectively collected data for the 12 months from March 1989. SETTING--Same day testing clinic run by the HIV/AIDS team at an urban teaching hospital. PATIENTS--561 consecutive people choosing to attend and proceeding to HIV-I testing. RESULTS--The demand for the service caused it to run to capacity within six months. The median age of those attending was 28 years and 65% (364 patients) were male. The overall prevalence of HIV-I infection was 3.9% (22 patients). The greatest prevalence was in men reporting their primary risk as homosexual contact (11.9%, 13/109). The median CD4 cell count in the 22 patients who had detectable HIV-I antibodies was 0.31 x 10(9) cells/l (normal range 0.5 x 10(9)/l to 1.2 x 10(9)/l). Twenty of these patients were asymptomatic (Centers for Disease Control stages II or III), 14 had CD4 cell counts below 0.5 x 10(9)/l. CONCLUSIONS--There is a recognisable demand for a service providing rapid results of HIV-I antibody testing in this setting. The overall seroprevalence of 3.9% is comparable with the 5.8% reported from freestanding clinics in the United States. Most patients with HIV-I antibodies detected in this way are asymptomatic but could benefit from early medical intervention because of low CD4 cell counts.